1983
DOI: 10.1111/j.1745-9125.1983.tb00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Class and Delinquent Behavior in a National Youth Panel: 1976–1980

Abstract: This article addresses the question of whether or not a more adequate measure of self-reported delinquency applied to a representative national sample would reveal class differences in r l e l i m that have not been found in earlier self-report studies. The methodolopacal criticisms of earlier self-report m asures are reviewed, a new self-report measure is described, annual sex-by-class-spei$fic prevalence and incidence rates based on this neu, memre are presented for a national youth panel for the years 1976 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
174
1
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 284 publications
(185 citation statements)
references
References 18 publications
6
174
1
4
Order By: Relevance
“…The present study indicates that at least as many women as men are violent toward their partners. These results corroborate previous surveys of community samples in the United States (Elliott et al, 1985;O'Leary et al, 1989;Straus & Gelles, 1986). The gender similarities are counterintuitive.…”
Section: Who Participates In Parmer Violence ?supporting
confidence: 82%
See 4 more Smart Citations
“…The present study indicates that at least as many women as men are violent toward their partners. These results corroborate previous surveys of community samples in the United States (Elliott et al, 1985;O'Leary et al, 1989;Straus & Gelles, 1986). The gender similarities are counterintuitive.…”
Section: Who Participates In Parmer Violence ?supporting
confidence: 82%
“…In contrast, surveys of birth cohorts such as ours, which sample the full range of involvement in partner violence, support generalizable conclusions about the epidemiology and correlates of partner violence. Our findings and other studies (Elliott et al, 1985;Straus & Gelles, 1986;Straus et al, 1980) have shown women to behave at least as violently as men. However, the interpretation of violent behavior perpetrated by men and women must be informed by knowledge about the consequences of violence, the context in which it occurred, the motives of perpetrators, and their personal characteristics.…”
Section: Who Participates In Parmer Violence ?supporting
confidence: 72%
See 3 more Smart Citations